Description of Reasons of People to Work as Government Employee - Franky Franky; Thomas Budiman (Journal of International Conference Proceedings (JICP), 2019)
The Indonesian society are still put respect and hope higher to one profession’s who work at the government agencies, in Indonesia they are known as Aparatur Sipil Negara (ASN). Based on this reason, the Indonesian government urged to have a new paradigm in recruiting their employees. By knowing factors that drives someone to choose ASN as their profession the government can get expertises both in skill and scholarly. This study has resulting some factors that affect respondents to join ASN such as their: current job, parent’s job, pension factor, low work load, and lastly proud. Their willing to join ASN mostly not affected by their: gender, present allowances, not because working as an ASN will be relaxed, not because of the allowance available, not because of their parents’ demand nor no dismissal. Respondents will not join the ASN because lack of fighting spirit and struggles. They will not join ASN because of lack of creativity, not because of bounded, not because hard resignation, not because of slow carier path nor the low salary rate. Among those factors which affect respondents to join ASN or not affecting is their present job. If their present job is not ASN or jobless, then the probability to become an ASN is 41.3%. If their present job is ASN or college students then the probability of desire to be ASN is 84.4%. The profile of the respondents who are desired to be ASN observed from Tree Diagram. The method used in this study are Crosstab and Classification Tree.